Novos leitores, novas habilidades de leitura e significação: Desafios para a media e information literacy - Cerigatto, Mariana Pícaro [UNESP]; De Casarin, Helen Castro Silva [UNESP] (My University, 2015)
Recognizing the importance of developing the information and media literacy in contemporary society, this article discusses the scenario of hybrid languages born on cyberspace, hypertext and the new types of readers who interact with information, now disseminated by digital media. As theoretical references authors such as Lucia Santaella, we develop arguments that present the headquarters of language and thought within a semiotic support. Matrices help to understand the phenomenon of hybrid language in hypertext. Therefore, we emphasize that the development of skills associated with the new reading environments propitiated by the virtual environment requires the understanding of language, which is one of the concepts used within the media and information literacy (MIL) proposal of Unesco, which combines the two concepts and skills of information and media literacy. It is hoped that this article motivate scholars and practitioners of education and information to take responsibility to educate for information environments that arise with new media and technologies, emphasizing the issue of reading and language.
New readers, new reading skills and meaning: Challenges for media and information literacy
Keywords: Hypertext; Matrices of language; Media and information literacy